The course of judo competition created by gold medalists of the World Judo Championships 2015 in Astana - Pujszo, R.; Adam, M.; Wolska, B. (Archives of Budo Science of Martial Arts and Extreme Sports, 2017)
Background & Study Aim: Characteristic features of technical-tactical preparedness of athletes who won the World Judo Championships are model values to estimate the starting effectiveness. The analysis of the manner the top athletes win during one of the most important sport events may acknowledge reference values. The aim of this study is knowledge about ways of contests leading to a victory only by gold medalists of the World Judo Championships (i.e. the athletes who won all the fights).